2021
DOI: 10.3390/cancers13205118
|View full text |Cite
|
Sign up to set email alerts
|

Pirfenidone Reduces Epithelial–Mesenchymal Transition and Spheroid Formation in Breast Carcinoma through Targeting Cancer-Associated Fibroblasts (CAFs)

Abstract: The aim of this study was to assess the effects of pirfenidone (PFD) on promoting epithelial–mesenchymal-transition (EMT) and stemness features in breast carcinoma cells through targeting cancer-associated-fibroblasts (CAFs). Using The Cancer Genome Atlas (TCGA) database, we analyzed the association between stromal index, EMT, and stemness-related genes across 1084 breast cancer patients, identifying positive correlation between YAP1, EMT, and stemness genes in samples with a high-stromal index. We monitored c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 70 publications
0
12
1
Order By: Relevance
“…For example, Cancer-associated broblasts (CAFs) can stimulate phenotypic transformation and secrete a broad range of growth factors [42]. In addition, in recent study, pirfenidone was regarded as potential drug in suppressing invasion and potentially metastasis in breast cancer [13]. Tumor-associated macrophages (TAMs) also could be induced M2-polarization by cytokines released by tumor cells [43].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, Cancer-associated broblasts (CAFs) can stimulate phenotypic transformation and secrete a broad range of growth factors [42]. In addition, in recent study, pirfenidone was regarded as potential drug in suppressing invasion and potentially metastasis in breast cancer [13]. Tumor-associated macrophages (TAMs) also could be induced M2-polarization by cytokines released by tumor cells [43].…”
Section: Discussionmentioning
confidence: 99%
“…To nd out better curative effect and explore more treatments methods, many researchers have reported that the expression of immune-related genes were different among immune cells and in uenced HNSCC patient prognosis [11,12]. Just like cancer-associated broblasts cell (CAFs), a common stromal cell, it has been reported play important roles in HNSCC progression and prognosis, such as participate in tumor cell proliferation, angiogenesis, and immunosuppression [13].…”
Section: Introductionmentioning
confidence: 99%
“…Finally, dynamic crosstalk between CAFs and cancer cells involve transfer of genetic messages such as ncRNA-loaded exosomes, and in this field, a lncRNA was recently characterized as participating in this process . Consequently, bearing in mind all these improvements, today CAFs represent a crucial therapeutic target for getting rid of the deleterious effects of EMT in invasive cancers (Es et al, 2021).…”
Section: Tumor Microenvironmentmentioning
confidence: 99%
“…Further, A549 lung cancer cells injected subcutaneously into mice with or without human CAFs showed that CAFs enhanced tumor growth in vivo (26). Another study analyzing data from 1084 breast cancer patients in The Cancer Genome Atlas (TCGA) observed a correlation between EMT, stemness, and samples with a high stromal index (35).…”
Section: Introductionmentioning
confidence: 99%